Integrated Control for State and Local Governmental Entities with an Eye to Fiscal Enhancements - Edward J. Lusk; Emeritus Emeritus; Michael Halperin (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
Abstract: The state and local governmental [SLG] accounting system is driven by a number of recording rules and regulations. These are codified by the Governmental Accounting Standard Board referencing related agencies such as the OMB and have been the basis of the recording rules in most countries. These recording rules can also be used as the basis for management monitoring and control in SLG entities. From this perspective, we examine the following five extensions of the usual SLG recording context that can be used to improve efficient and effective use of the resource committed to those in charge of the governmental system. To this extent then the following considerations pertain to any SLG in the global context: 1. Extending Prudent Stewardship, 2. Central Procurement: Negotiation Leverage, 3. Recording the Budget, Appropriations, Allocations, Allotments and Encumbrances, 4. Tracking Accountability in the GCA&GLTL Groupings, and 5. Calibrating Early Payment Status [EPS] Discounts. We conclude with two further interesting issues for future research.